Предмет: Алгебра, автор: FeIiks

Даю 35 баллов!
Спрости вирази:

Приложения:

Ответы

Автор ответа: yer21k
1

Ответ:

a) \:  {a}^{2} (1 + 2a +  {b}^{2} ) - ( {a}^{2}  {b}^{2}  +  {a}^{2} ) =  {a}^{2}  + 2 {a}^{3}  +  {a}^{2}  {b}^{2}  -  {a}^{2}  {b}^{2}  -  {a}^{2}  = \boxed{  \bold{2 {a}^{3}}} .

b) \: 4xy(2x - y) - 2x(4xy - 1) = 8 {x}^{2} y - 4x {y}^{2}  - 8 {x}^{2} y + 2x = \boxed{  \bold{2x - 4x {y}^{2}}} .

c) \:  - 2 {m}^{2}  {n}^{3} (4m {n}^{2}  - 8 {m}^{2} n) - (4 {m}^{2}  {n}^{2} ) {}^{2}  =  - 8 {m}^{3}  {n}^{5}  + 16 {m}^{4}  {n}^{4}  - 16 {m}^{4}  {n}^{4}  =  \boxed{ \bold{ - 8 {m}^{3}  {n}^{5}}} .


FeIiks: спасибо огромное
Похожие вопросы
Предмет: Английский язык, автор: ekaterina282990